2021
DOI: 10.1016/j.molstruc.2020.129390
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potential drug from Azadirachta Indica (Neem) extracts for SARS-CoV-2: An insight from molecular docking and MD-simulation studies

Abstract: Highlights 19 compounds from Neem extract tested against 7 standard anti-COVID drugs for action on PLpro of latter All 19 NEEM molecules show better docking, ADME results vis-a-vis standard drugs Among the 19, desacetylgedunin (DCG) gives highest docking score with PLpro MD simulation of shows binding with DCG induces large structural change on PLpro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 21 publications
0
73
0
Order By: Relevance
“…Altogether, these results demonstrated that Neem exhibits multidimensional therapeutic applications and can also be a potential therapeutic option against COVID-19. Recently, a study demonstrated that A. indica showed significant inhibitory activity against papain like proteases PLpro of SARS-CoV-2 [178]. Among various compounds, desacetylgedunin (DCG) showed highest binding affinity against PLpro [178].…”
Section: Anti-viral Potential Of Azadirachta Indicamentioning
confidence: 99%
“…Altogether, these results demonstrated that Neem exhibits multidimensional therapeutic applications and can also be a potential therapeutic option against COVID-19. Recently, a study demonstrated that A. indica showed significant inhibitory activity against papain like proteases PLpro of SARS-CoV-2 [178]. Among various compounds, desacetylgedunin (DCG) showed highest binding affinity against PLpro [178].…”
Section: Anti-viral Potential Of Azadirachta Indicamentioning
confidence: 99%
“…Azadirachta indica (Neem), an indigenous Indian medicinal plant used in Traditional Indian Medicine, has been reported of remarkable antiviral potency against avian influenza virus, bursal disease virus, Newcastle disease virus, group B coxsackievirus, dengue virus type-2, duck plague virus, poliovirus type-1 and bovine herpes virus type-1 [ 97 ]. Neem has been extensively used to treat asthma, cough, fever and diarrhea in Ayurvedic system of medicine; these are the most prevalent symptoms in SARS-CoV-2 infection [ 98 ].…”
Section: Molecular Scaffolds From Mother Nature With Possible Anti-sars-cov-2 Potentialmentioning
confidence: 99%
“…Using the traditional knowledge of viral pathogenesis, pharmacodynamics of drugs [23] , different synthetic compounds [24] and using of computational tools many drugs are currently in pipeline to be repurposed for combating the SARS-CoV-2 [22] . Again following the same techniques different plant extracts are used for the treatment of COVID-19 [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%